Medical Education in Pathology: General Concepts and Strategies for Implementation. - Koch, Lisa K.; Chang, Oliver H.; Dintzis, Suzanne M. (Archives of Pathology & Laboratory Medicine, 2021)
* Context.--Pathology education must evolve as medical knowledge expands and disruptive technologies emerge. The evolution in pathology teaching practices accelerated as traditional teaching modalities were suspended in March 2020 during the coronavirus disease 2019 (COVID-19) pandemic. Objectives.--To provide pathologists an overview of established teaching paradigms and practical examples of how these paradigms may be applied to pathology education, emphasizing differences in graduate and undergraduate medical education as well as the challenges and promises of remote learning, as revealed by the COVID-19 pandemic. Data Sources.--Selected peer-reviewed publications representing the field of educational social science. Conclusions.--Evidence-based methods described in education and social sciences can be effectively deployed in pathology education and especially remote learning, as necessitated by the current COVID-19 pandemic. Understanding established principles, such as cognitive load, competency-based learning, peer-assisted learning, and flipped classrooms may prove useful in developing effective, learner-centric content for pathology education.